STUDI PROBABILITAS GEMPA DAN PERBANDINGAN ATENUASI PERCEPATAN TANAH METODE JOYNER DAN BOORE (1988), CROUSE (1991) DAN SADIGH (1997) DI SEKITAR WILAYAH BANDA ACEH DAN BENGKULU - Palupi, Indriati Retno; Raharjo, Wiji; Santoso, Agus (BERKALA FISIKA, 2015)
Sumatera is one island in Indonesia which is located near subduction zone. It is prone of earthquake, but the level of prone is not same in each province on its, like in Banda Aceh and Bengkulu. Both of them are the site of this research. Probability is one way to know characteristic or earthquake distribution on both of the site. Earthquake distribution inÂ  Aceh is more convergence than Bengkulu. It means that earthquakeâ€™s number in Aceh is more than in Bengkulu. It is done for fault source and area source of earthquake. Ground motion because of earthquake can display by acceleration and attenuation curve. It can be calculated by Joyner & Boore (1988), Crouse (1991) and Sadigh (1997) method. Keywords: PSHA, acceleration, Joyner & Boore (19988), Crouse (1991) and Sadigh (1997) method